Application of antimicrobial treatment to whole carcasses during prechill can improve microbial quality of broiler parts. Issue 2 (15th January 2018) - Steininger, Charlotte G.; Harrison, Mark A.; Berrang, Mark E.
Abstract: Broilers cut up into parts have been reported to have higher microbial numbers than corresponding whole carcasses. Prechill immersion leads to water uptake by whole carcasses which is released during cut‐up. The objective of this study was to determine if an antimicrobial treatment applied during prechill can reduce the prevalence or numbers of total aerobic bacteria and Escherichia coli on corresponding chicken parts. Commercially eviscerated broiler carcasses were subjected to sequential immersion prechill, final ice water chill, and cut‐up procedures. Enumeration of total aerobic bacteria, coliforms, and E. coli was performed using carcass rinses at postevisceration, after 15 min prechill (22–25°C water), after 30 min ice water immersion chill (0–4°C water), and following cut‐up into parts. Six prechill, antimicrobial treatments were evaluated: 50 ppm chlorine, 50 ppm chlorine + 0.5% T‐128 (a chlorine stabilizer), 20 ppm peracetic acid, 20 ppm peracetic acid + 0.5% T‐128, 0.5% T‐128, and water. Addition of 0.5% T‐128 to water, 20 ppm peracetic acid, or 50 ppm chlorine during prechill significantly ( p  < .05) decreased total aerobic bacteria and E. coli /coliforms following prechill by ∼1.5–2.0 log compared to the water control. Practical applications: Antimicrobial treatment of whole broiler carcasses during prechill is a practical means to lessen microbial contamination of corresponding broiler parts. Chlorine and peracetic acid applied with a chlorine stabilizer (T‐128) can be expected to be effective for this purpose.